EP1293 Medical treatment of vaginal intraepithelial neoplasia (VaIN): evaluating the efficacy and safety of 5-flouorouracil (5-FU). (1st November 2019) - Tranoulis, A; Georgiou, D; Founta, C; Sayasneh, A; Nath, R
Abstract : Introduction/Background: Medical treatment has gained popularity as an alternative treatment option in vaginal intraepithelial neoplasia (VaIN). The aim of this meta-analysis was to ascertain the efficacy and safety of 5-flouorouracil (5-FU) in this context. Methodology: A literature search was conducted throughout the PubMed, EMBASE, SCOPUS, ClinicalTrials.gov, and Cochrane Databases for relevant studies from inception until September 2019. We computed the summary proportions of women treated for VaIN with 5-FU for the outcomes of complete response and recurrence by random-effects meta-analysis. Sub-group analyses were performed to address heterogeneity. Results: 14 observational studies were included. The studies were of moderate quality. Pooled results from 14 studies enrolling 358 VaIN women rendered a summary proportion of 82.18% (95% CI 69.80% - 88.82%) for the outcome of complete response. Pooled results from six studies enrolling 184 high-grade VaIN women rendered a summary proportion of 77.53% (95% CI, 59.90% - 91.15%) for the outcome of complete response. Pooled results from five studies enrolling 26 VaIN women rendered a summary proportion of 53.92% (95% CI 34.62% - 72.61%) for the outcome of complete response amongst persistent lesions. Pooled results from six studies enrolling 98 VaIN women rendered a summary proportion of 16.42% (95% CI, 7.39% - 28.14%) for the outcome of recurrence. The agent was well tolerated by most women and only few studies reported discontinuation of the treatment owing to severe adverse effects. Conclusion: 5-FU is seemingly an effective and safe treatment modality in the treatment of VaIN. It can be considered as an alternative conservative treatment option, leading to less aggressive and morbid interventions, especially amongst young women with multifocal lesions. Further studies with longer follow-up will be warranted to further assess its efficacy and safety in this setting. Disclosure: Nothing to disclose